A cross-sectional assessment of the Omega-3 Index in an Australian cohort of elite rugby football athletes: Opportunities to address nutritional omega-3 intake - Peoples, G. E.; Anthony, R.; Freney, E.; Jaffrey, N.; Cronin, S.; Macartney, M. J. (The Journal of Sport and Exercise Science, 2025)
Rugby football athletes endure unique physiological strain including high intensity contacts. Long chain omega-3 polyunsaturated fatty acids (LCn-3PUFA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are incorporated into cell membranes and optimise cell durability. However, it is unclear whether elite rugby football athletes consume enough EPA and DHA to optimise their omega-3 status. This study evaluated omega-3 biomarker status (Omega-3 Index [O3I]; sum of erythrocyte EPA% + DHA%) and principal LCn-3PUFA dietary habits of elite athletes (n = 100; 54% female; mean age 25 years; 95% CI [24, 26]; mean body mass 89 kg; 95% CI [86, 93]) in a cohort of Rugby Australia (RA) and National Rugby League (NRL). At the start of their competition cycle, 47 RA (64% female) and 53 NRL (45% female) athletes had their whole blood collected using a finger prick method and analysed to produce a fatty acid profile. At the same time, n = 96 of these athletes completed a nutritional omega-3 survey. The mean cohort O3I was 5.38% (95% CI [5.15, 5.60]; optimal > 8%) and arachidonic acid (AA) to EPA ratio (AA/EPA) was 13.21 (95% CI [12.28, 14.14]; optimal < 11). There was no association of rugby code on the sum of the major classes of fatty acids. The male athletes` O3I was significantly higher (6.06%; 95% CI [5.89, 6.23] vs. 4.79%; 95% CI [4.56, 5.02]; p < 0.001) and AA:EPA was significantly lower (11.44; 95% CI [1.48, 21.40] vs. 14.90; 95% CI [14.76, 15.04]; p = 0.001) than the females, respectively. Australian rugby athletes who self-reported EPA + DHA intake above 500 mg / day were observed to have a significantly elevated O3I. Notwithstanding, given that only two athletes returned an O3I > 8%, there are opportunities for sports dietitians to address nutritional LCn-3PUFA intake in this cohort.